Parametric design and daylighting: a literature review - Eltaweel, Ahmad; Su, Yuehong (Elsevier, 2017)
In the history, architecture was exploited to the human being to protect him from unsteady environmental conditions. In the past centuries, architecture was pioneer art which has special features such as; simplicity, organization, clear style, accurate decoration, material assembly, and so on. However, modern buildings become complex products that have so many parts which have to fulfil different functions. Therefore, new computational ways and techniques have been developed to facilitate the design of modern complicated buildings and to create a convenient quantitative relationship between the environment and the envelope, putting into consideration the obstacles which influence on the building design. This has therefore formed the concept of parametric design in architecture, in order to deal with complex designs and gain more accurate results. Modern architects claim that parametric design is the most creative way to understand the development and complexity of the new era of architectural trends [1]. Meanwhile, it is really hard to deal with sophisticated details in buildings using our brains to imagine, or conventional ways to design [2]. In addition, building technologies nowadays are integrated and containing many disciplines in the same time, and each discipline is dependent on the other disciplines in a very complex vast connections. Hence, they should be organized in a database container, and this container could be managed parametrically using parametric design as an advanced way to explore and understand these sophisticated relations [3]. This paper hence presents a literature review on parametric design in architecture practice and put a focus on its applications in daylighting and solar radiation, which can have an essential impact on improving daylight availability and energy saving.